2010
DOI: 10.1016/j.jvs.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Open and endovascular repair of type B aortic dissection in the Nationwide Inpatient Sample

Abstract: For patients with a diagnosis of T(B)AD who undergo repair, the endovascular approach is being used for older patients with greater comorbidities, yet has reduced morbidity and in-hospital mortality. The use of endovascular stent graft repair for type B thoracic aortic dissection merits further longitudinal analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 34 publications
4
105
0
Order By: Relevance
“…4,7,8,24,27,30 Nevertheless, 19% (9% type A and 33% type B) of our patients required surgical or endovascular therapy during follow-up with interventional mortality similar to those reported in other series. 6,8,25,31 Overall mortality in our study was 5% at 3 years, 13% at 5 years, and 48% at 10 years (20% in type A and 36% in type B), similar to those of contemporary series from major aortic surgery institutions. 6,7,23,26 -29 …”
Section: Long-term Evolution In Type a And B Dissections With Patent supporting
confidence: 84%
“…4,7,8,24,27,30 Nevertheless, 19% (9% type A and 33% type B) of our patients required surgical or endovascular therapy during follow-up with interventional mortality similar to those reported in other series. 6,8,25,31 Overall mortality in our study was 5% at 3 years, 13% at 5 years, and 48% at 10 years (20% in type A and 36% in type B), similar to those of contemporary series from major aortic surgery institutions. 6,7,23,26 -29 …”
Section: Long-term Evolution In Type a And B Dissections With Patent supporting
confidence: 84%
“…Thus, INSTEAD-XL corroborates recent observational evidence, suggesting longterm beneficial results of TEVAR in subacute and chronic dissection. 4,12,25 With safer procedures attributable to improved operator skills and better technology, TEVAR may emerge as first-line therapy of type B dissection; the attempt to heal and remodel dissected aorta may replace the current complicationspecific strategy. ) and Landmark analysis with a breakpoint at 24 months after randomization to the end of the trial are shown for optimal medical treatment (OMT) and OMT + thoracic endovascular aortic repair (TEVAR) groups.…”
Section: #15 (Nr-2421) Cancermentioning
confidence: 99%
“…Our team usually introduces a 150-mm long stent graft first, and, if needed, distal or proximal extension is performed in the second period. Results from treating complicated type B aortic dissection document the success of TE-VAR with only 10.6% mortality, as compared with 19.5% mortality for surgical treatment [22]. When TEVAR is used in complicated dissections, there is a documented decrease in the incidence of spinal ischemia to 2% versus 8% when surgery is used [18,23].…”
Section: Discussionmentioning
confidence: 98%
“…The patient gradually rehabilitated to a Rankin score of 3 and died of myocardial infarction (MI) in the 4th month after treatment. The published frequency of this complication in large cohorts of patients ranges from 0-10% [16,18,21,22].…”
Section: Discussionmentioning
confidence: 99%